Fresh Osteochondral Allograft Transplants in the Knee: Bipolar and Beyond - Stannard, James P.; Stannard, James T.; Schreiner, Anna J. (The Journal of Knee Surgery, 2020)
Knee patients who have sustained chondral and osteochondral lesions suffer from debilitating pain, which can ultimately lead to posttraumatic osteoarthritis and whole-joint disease. Older, nonactive patients are traditionally steered toward total knee arthroplasty (TKA), but younger, active patients are not good candidates for TKA based on implant longevity, complications, morbidity, and risk for revision, such that treatment strategies at restoring missing hyaline cartilage and bone are highly desired for this patient population. Over the past four decades, fresh osteochondral allograft (OCA) transplantation has been developed as a treatment method for large (> 2.5 cm2) focal full-thickness articular cartilage lesions. This article documents our own institutional OCA journey since 2016 through enhanced graft preservation techniques (the Missouri Osteochondral Preservation System, or MOPS), technical improvements in surgical techniques, use of bone marrow aspirate concentrate, bioabsorbable pins and nails, and prescribed and monitored patient-specific rehabilitation protocols. Further follow-up with documentation of long-term outcomes will provide insight for continued optimization for future applications for OCA transplantation, potentially including a broader spectrum of patients appropriate for this treatment. Ongoing translational research is necessary to blaze the trail in further optimizing this treatment option for patients.
Keywords: lesions; osteochondral allograft transplantation; allograft preservation methods; surgical techniques; patient-specific rehabilitation protocols